Hubungan Pekerjaan Ibu, Inisiasi Menyusu Dini (IMD) dan Dukungan Keluarga dengan Pemberian ASI Eksklusif di Wilayah Kerja Puskesmas Punti Kayu Palembang Tahun 2022 - Riya Trisnawati; Siti Aisyah Hamid; Eka Afrika (Universitas Batanghari Jambi, 2023)
Exclusive Breastfeeding is essential for the survival of the baby. Because breast milk contains natural proteins found in the body (Growth factor) and antibody substances. Growth factors in breast milk have an important role in helping the maturation process of organs and hormones, while antibody substances help the maturation process of the immune system. Since the process of maturation of the system in newborns is rudimentary. To find out the relationship between mothers' work, Early Breastfeeding Initiation (IMD) and partial family support with exclusive breastfeeding in the Work area of the Punti Kayu Health Center, Palembang City in 2022. This study uses a type of analytical survey research where independent variables and dependent variables are collected at the same time. With a Cross sectional approach, which aims to find out the Indepedent variables, namely maternal work, IMD and family support and dependent variables for exclusive breastfeeding success. The sample was taken according to the inclusion criteria of 42 respondents using the accidental sampling method. Data analysis using univariate, bivariate analysis, namely the chi-square test. Based on the results of the chi-square statistical test, it can be concluded that there is a relationship between the mother's work obtained a p-value of 0.154, Early Breastfeeding Initiation (IMD) with a p-value of 0.002, and family support with a p-value of 0.002. There is a meaningful relationship between mother's work, IMD and family support simultaneously with exclusive breastfeeding at the Punti Kayu Palembang Health Center in 2022.